Importance of movement symmetry in technical and tactical preparation of high advanced judokas different level of mastership - Starosta, W. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. The equalizing level of judokas preparation and more tough international competition force to seek continuously for reserves. The dimishing reserves still remaining in fitness draw attention to technical and tactical preparation. Here, movement symmetry and its application in tactics have been little used, as yet. The objective was to determine appearance of movement symmetry its extent and importance for sport successes by judokas. Methods and material. general physical fitness tests, interviews, observations. Tested were 136 advanced judokas (male and female), mainly juniors (finalists of the Polish Youth Games, reserve of the Polish Junior National Team). Results were given on the background of literature data for 959 judokas from various countries. Results. Investigation of the large judokas group has shown domination of right-side body activity, especially in young judokas (threefold in juniors). Over 20% of leading judokas made throws in both directions, with their number increasing with increase in sport proficiency (up to 57.3% among medal winners, and 71.4% among golden medal winners during various events, including Olympic Games). Symmetrically trained judokas have had greater successes when using right and left throws. This points to the increasing important of movement versatility at the highest level of sports mastery. Conclusion. Physical fitness test results in judokas show a differentiation in the body sides abilities in particular tests. This differentiation has been the highest in balance, flexibility and global movement coordination tests and lowest in the force (speed type tests).